한국과 미국의 초등학교 과학 교과서 분석 - 김효남; Hyo Nam Kim; 박도영; Do Yong Park (과학교육연구지, 2009)
과학교과서는 한국과 미국에서 가장 많이 쓰이는 교수 학습 자료이다. 과학교육목표와 과학교과내용의 특징을 분석하기 위하여 한국과 미국의 초등학교 과학 교과서를 분석하였다. 한국과 미국의 1학년과 4학년 과학 교과서 각각100 쪽을 무작위로 선택하여 과학교육목표를 분석하였다. 1학년에서 6학년까지의 생명 영역의 과학 내용이 분석되었다. 한국의 1학년 과학내용은 슬기로운 생활 교과서를 분석하였는데, 슬기로운 생활 교과는 과학교과와 사회교과의 통합교과이다. 미국에서 많이 쓰이고 있는 초등학교 교과서 중 하나인 Harcourt Science의 1학년과 4학년 교과서를 분석하였다. 과학교육목표분석체계는 과학 지식, 과학적 탐구, 과학적 태도, STS, 그리고 과학 철학과 역사로 구성되어 있다. 한국과 미국의 초등학교 과학 교과서의 내용을 분석한 결과는 다음과 같다. 미국의 초등학교 과학 교과서는 과학적 탐구 보다 과학 지식을 더 많이 포함하고 있었다. 한국의 과학 교과서는 과학 지식 보다는 과학적 탐구를 더 많이 포함하고 있었다. 미국의 초등학교 과학 교과서는 생명 영역의 일부 주제에 대하여 한국 보다 더 어려운 내용을 다루었고, 세포나 생태계의 종류에 대해서는 여러 학년에 걸쳐 반복적으로 다루고 있는 것으로 분석되었다. Science textbook is the most frequently used teaching material in elementary schools of the United States and Korea. Elementary science textbooks of the United States and Korea are analyzed to find out the educational objectives and characteristics of contents shown in textbooks. About 100 pages each in the first grade and fourth grade science textbooks each nations are selected randomly for educational objective analysis. Life science contents of 1st to 6th grade are analyzed from elementary science textbooks of the United States and Korea. The analyzed textbooks in Korea are `Wise life,` an integrated subject with social studies and science, and `science.` The analyzed elementary science textbooks of the United States are Harcourt Science, which is one of the frequently used textbooks. The educational objective framework used includes science knowledge, scientific inquiry, scientific attitude, STS, and philosophy and history of science. The results show science textbooks of the United States emphasize scientific knowledge more than scientific inquiry. Korean science textbooks emphasize scientific inquiry more than scientific knowledge. Elementary science textbooks of the United States present some life science topics redundantly and expose more difficult topics than Korean.